2014
DOI: 10.4172/2161-0665.1000196
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence and Etiology of Anterior Cruciate Ligament Injuries in Patients under the Age of 18 in the State of Wisconsin

Abstract: Background: ACL injuries can have long-term effects on the musculoskeletal system, causing early osteoarthritis, and are of particular concern in children and adolescents as competitive sports participation increases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Another study also found younger patient age who suffered ACL injury, which was athletes [ 7 ]. This condition appeared as a result of trauma or sports injury on younger age patient [ 8 , 9 ]. Additionally, Mei et al [ 6 ] found that 80% of male non-athletes developed ACL injury from basketball and soccer games.…”
Section: Discussionmentioning
confidence: 99%
“…Another study also found younger patient age who suffered ACL injury, which was athletes [ 7 ]. This condition appeared as a result of trauma or sports injury on younger age patient [ 8 , 9 ]. Additionally, Mei et al [ 6 ] found that 80% of male non-athletes developed ACL injury from basketball and soccer games.…”
Section: Discussionmentioning
confidence: 99%
“…The delay of medical treatment is an important prognostic factor in ACL injury cases [ 13 ]. If the treatment is delayed, the chance of secondary meniscal tear and subsequent cartilage defect will be higher compared to early treatment [ 14 , 15 , 16 ]. Mean treatment delay in this study is 8.5 months.…”
Section: Discussionmentioning
confidence: 99%
“…1 Studies showed that if ACL tears are managed conservatively there is increased incidence of meniscal tears and early arthritic changes in the knee joint. 2 The reason to repair a torn ACL is to provide knee stability, painless range of motion and to prevent osteoarthritis. The gold standard for ACL autograph reconstruction is bone patella tendon bone (BTB).…”
Section: Discussionmentioning
confidence: 99%
“…Maximum contraction of the knee musculature significantly reduces anterior translation of the tibia in men and women compared with relaxed and contracted states. 2 Women experience ACL tears up to nine times more often than men. 3 This high incidence in females may related due to the increasing trend of girls towards sports.…”
Section: Introductionmentioning
confidence: 99%